How do we keep them coming back? A look at individual factors impacting attendee satisfaction and intention to return to festivals. Issue 2 (5th June 2017) - Pope, Jennifer Angela; Isely, Paul; Agbetunsin, Busuyi
Abstract : Purpose: The purpose of this paper is to analyze the factors that influence the level of satisfaction or festival attendees and how that influences their intention to return. The impact of other factors such as past attendance and distance traveled to the festival were also examined. Design/methodology/approach: The data for this study were collected using an online survey from attendees at a LaughFest™, a comedy festival hosted as a fund and awareness raiser for a non-profit organization (NPO) in a medium-sized Midwestern city. The data related to reasons for level of satisfaction and intention to return were coded into dichotomous variables, and along with income, gender and distance traveled to the event were analyzed using logistic regression. Findings: Of the factors that impacted satisfaction, performers, venue, and ticket prices were found to have the largest impact on intention to return, with negative experiences having a greater impact than positive. Previous attendance was also significant with regard to intention to return. Practical implications: This information will allow this festival's managers to target specific areas for improvement to increase the rate of repeat attendance. Originality/value: This paper aims to contribute to the literature addressing specific factors influencing level of satisfaction and how those factors impact intention to return by examining them in a comedy festival that is also a fund and awareness raiser for a local NPO. There are few studies examining this aspect in regard to this particular type of festival.